Analysis of Outpatient Patient Satisfaction at Jayagiri Health Center, Lembang Village, West Bandung District - Putri, Meilinda Eka; Hadithya, Riyan (Universitas Ibn Khaldun Bogor, 2024)
The success of a company depends on how well its customers remain satisfied when using the products and services offered. Similarly, in the context of healthcare services, a hospital's positive or negative reputation is often determined by the patients' evaluations during inpatient or outpatient care. The method used in this study is a qualitative descriptive method, which aims to understand the phenomena experienced by the research subjects. The study found that the highest value of the satisfaction variable is two and is found in the question